Risk Tolerance, Overconfidence and Investment Decisions in Nepal - Pitambar Lamichhane; Arogya Simkhada (MASI Mandiri Edukasi, 2024)
In the present globalized, modernized and digitalized business environment, investors are attracted to the stock market for their investment in financial assets rather than real assets. Investors' Investment decisions are affected by various factors affecting their investment in financial assets in the stock market. This research intends to address problems of how investors’ psychological factors (risk attitude & overconfidence) influence their investment decisions. Therefore, this paper examines the impact of investors’ risk tolerance capacity and overconfidence level on investors’ investment decisions in Nepal. This study has applied descriptive and causality (regression) research designs to investigate the effect of risk tolerance and overconfidence on investment decisions based on financial behavior theories. Data were obtained through the structured questionnaire survey. Investment decision-making is considered a dependent variable in this research, and risk tolerance and investors' overconfidence levels are used as explanatory variables. The correlation result reveals positive associations between explanatory variables and investment decisions. The regression result of this research study concludes that risk tolerance capacity and overconfidence level both significantly impact investors’ investment decisions in the Nepalese stock market. Therefore, policymakers, regulatory bodies, decision makers, market traders, and academics should focus on investors’ risk tolerance ability and overconfidence level to enhance investors' ability to make sound investment decisions to maximize their returns and minimize risk in Nepal.